Analysis of the relationship between earthquake-related losses and the frequency of child-directed emotional, physical, and severe physical abuse in Haiti. (August 2020) - Subedi, Sony; Davison, Colleen; Bartels, Susan
Abstract: Background: Child abuse is a public health and human rights issue that is prevalent worldwide. All forms of abuse against children can have negative physical and mental health consequences. Under post-disaster situations, where there is a potential for increased stress and decreased social support among caregivers, the risk of child abuse may be higher. Objective: To explore the association between earthquake-related losses (family-related and property-related) and the experience of emotional, physical, and severe physical child abuse in the household for children aged 2–14 in Haiti. Methods: A nationally representative sample of Haitian households from the 2012 Demographic and Health Survey (DHS) was used. Descriptive analyses were summarized using frequencies and measures of central tendency. Associations between earthquake-related loss and child abuse was assessed using log-binomial regression modelling. Results: Two years following the earthquake, and after considering potentially confounding variables, death of a household member was associated with a higher likelihood of a child being victim to emotional (RR = 1.11, 95 % CI: 1.05−1.17) and severe physical abuse (RR = 1.50, 95 % CI: 1.15−1.96). Conversely, injury of a household member was associated with a lower likelihood of a child experiencing emotional abuse (RR = 0.93, 95 % CI: 0.87−0.99). Conclusions: There were associations between earthquake-related losses and some forms of child abuse; the results were not consistent across all exposures and outcomes. The high prevalence of reported child abuse indicates a need for interventions to reduce child abuse in homes overall. There is also need for further research into the aetiology and influences specific to different types of abuse.